Making the World a Better Place by Creating Eco-Friendly Products and Customers Adoption Intentions: A Mediating Role of Perceived Product Eco-Friendliness - Khurshid, Muzammil; Abdullah, Muhammad; Azeem, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to explore the role of eco-friendly products and the customers’ adoptions towards those products through uncovering the probable mediating role of perceived product eco-friendliness. Nevertheless, companies are considering green marketing as an effective way to promote business ideas, and ultimate products & services. In the prevailing economic climate the companies are focusing on the influencing consumers towards green products because the said is driving factor for eco-friendly production. This study intends to analyze the moderating role of eco-friendliness in the relationship between customer adoption intentions towards those products furthermore, the impact of customers’ adoption of those eco-friendly through the eco-friendliness. Using the concept of marketing management, companies strive to cover long-term customer retention through better marketing performance. Eco-friendly production is a relatively new precautionary environmental strategy that seeks to increase the efficiency of the product, process, and service resources and ultimately reduces the risk to people and the relative environment as well.